ACE-2 in the highlight of COVID-19, A proposed pathology and potential correlations - Sorour, Khaled; Sarhan, Hossam; El-Menshawy, Hadeer (My University, 2020)
Pneumonia caused by the novel corona virus has derived the whole world into an emergency situation, bringing to mind similar epidemics including H1N5, dengue, SARS-CoV and MERS. Although SARS-CoV-2 didn't result in such a huge number of deaths when compared to, for example, Spanish influenza, it is categorized as having high infectivity rate. The trials to control the spread of the virus are often challenged by the lack of knowledge which means more time is needed to build a view regarding the pathological actions of the virus in order to properly target it. Recent reports declared that SARS-CoV-2 uses ACE-2 as a means to infect cells. This paper aims at addressing briefly the protective roles of ACE-2 in the lungs and the brain based on previous literature review and studies on other viruses that also use ACE-2 as a target for cellular entry. We hypothesized that COVID-19 pathology may be a consequence of viral Mediated down-regulation of ACE-2. In addition, we provided insights on the potential correlation between COVID-19 severity and male gender or smoking.
Keywords: Epidemiology; Life Sciences; Medicine and Health Sciences; Public Health